The Association between Depressive Symptoms and Non-Psychiatric Hospitalisation in Older Adults - Prina, A. Matthew; Deeg, Dorly; Brayne, Carol; Beekman, Aartjan; Huisman, Martijn (PLOS ONE, 2012)
Background It is known that people who suffer from depression are more likely to have other physical illnesses, but the extent of the association between depression and non-psychiatric hospitalisation episodes has never been researched in great depth. We therefore aimed to investigate whether depressed middle-aged and older people were more likely to be hospitalised for causes other than mental illnesses, and whether the outcomes for this group of people were less favourable. Methods & Findings Hospital events from 1995 to 2006 were obtained from the Dutch National Medical Register and linked to participants of the Longitudinal Aging Study Amsterdam (LASA). Linkage was accomplished in 97% of the LASA sample by matching gender, year of birth and postal code. Depression was measured at each wave point of the LASA study using the Centre for Epidemiologic Studies Depression (CES-D). Hospital outcomes including admission, length of stay, readmission and death while in hospital were recorded at 6, 12 and 24 months intervals after each LASA interview. Generalised Estimating Equation models were also used to investigate potential confounders. After 12 months, 14% of depressed people were hospitalised compared to 10% of non-depressed individuals. There was a 2-fold increase in deaths while in hospital amongst the depressed (0.8% vs 0.4%), who also had longer total length of stay (2.6 days vs 1.4 days). Chronic illnesses and functional limitations had major attenuating effects, but depression was found to be an independent risk factor for length of stay after full adjustment (OR = 1.33, 95% CI: 1.22–1.46 after 12 months). Conclusions Depression in middle and old age is associated with non-psychiatric hospitalisation, longer length of stay and higher mortality in clinical settings. Targeting of this high-risk group could reduce the financial, medical and social burden related to hospital admission.